Cost Variation in Temporizing External Fixation of Tibial Plateau and Pilon Fractures: Is There Room to Improve?. Issue 8 (August 2022) - Okelana, Bandele; McMillan, Logan; Huyke-Hernandez, Fernando A.; Only, Arthur J.; Parikh, Harsh R.; Cunningham, Brian P.
Highlights: There is large cost variation in temporizing external fixation management. Cost drivers included surgeon bias and implant preference, with external fixator clamps contributing most significantly to construct costs. Traumatologists produced significantly cheaper constructs for pilon fractures ( p =0.05) but not for plateau fractures ( p =0.85). There was no difference in construct cost or components between cases that underwent unplanned reoperation versus those that did not. Introducing construct standardization will contain healthcare spending without sacrificing patient outcomes. Abstract: Introduction: External fixator costs have been shown to be highly variable. Current information on external fixator costs and cost drivers is limited. The aim of this study was to examine the cost variation as well as the patient-, injury-, and surgeon-related cost drivers associated with temporizing external fixation constructs in tibial plateau and pilon fracture management. Materials and Methods: A retrospective review was conducted to identify isolated tibial plateau and pilon fractures treated with temporizing external fixation from 2006-2018 at a level 1 trauma center. Inclusion criteria were based on fractures managed with primary external fixation, skeletal maturity, and isolated ipsilateral fracture fixation. Fracture patterns were identified radiographically using Schatzker, Weber, and OTA classification systems. Implant costs were determined using direct purchase price from the institution. The primary outcome was the external fixator total construct cost. Clinical covariates and secondary outcomes, namely unplanned reoperations, were extracted. Factors associated with cost (i.e. cost drivers) were identified via multivariable regression analysis. Results: A total of 319 patients were included in this study (121 tibial plateau and 198 pilon fractures). Mean plateau construct cost was $5, 372.12 and mean pilon construct cost was $3, 938.97. Implant cost correlated poorly with demographic (r 2 =0.01 & r 2 =0.01), injury-independent (r 2 <0.01 & r 2 =0.03), and fracture pattern classifications (r 2 =0.03 & r 2 =0.02). Traumatologists produced significantly cheaper implants for pilon fractures ( p =0.05) but not for plateau fractures ( p =0.85). There was no difference in construct cost or components between patients that underwent unplanned reoperation and those that did not for both tibial plateau ( p >0.19) and pilon ( p >0.06). Clamps contributed to 69.9% and 77.3% of construct costs for tibial plateau and pilon, respectively. The most cost-efficient fixation constructs for tibial plateau and pilon fractures were the following respectively: of 5 clamps, 2 bars, and 4 pins; and of 4 clamps, 2 bars, and 3 pins. Conclusions: There is large cost variation in temporizing external fixation management. Cost drivers included surgeon bias and implant preference as well as use of external fixator clamps. Introducing construct standardization will contain healthcare spending without sacrificing patient outcomes. LEVEL OF EVIDENCE: Level III. Retrospective Cohort